Laser characterization for 3D imaging sensor - Thaboot, Kodchakorn (2024)
The master thesis focuses on the comprehensive characterization of the Time-of-Flight (ToF) module, which incorporates two Vertical Cavity Surface Emitting Laser (VCSEL) sources functioning as emitters. The primary objective of this characterization is to ensure that the VCSELs operate as expected and meet the required specifications for their intended applications.